Altruism And Local-Based Social Cooperation in The Bagarumutan Tradition of Banjar People, South Kalimantan - Saputra, Riza (Proceedings of International Conference on Muslim Society and Thought, 2024)
This research delves into the forms of social cooperation and altruism in the cultural context of Banjar society, with a specific focus on the practice of the bagarumutan tradition. To gain a deeper understanding of this social phenomenon, a qualitative approach was employed through a series of participant observations, in-depth interviews with community members, and analysis of related local narratives. The results of the study indicate that altruism, as a core value driving social actions, is manifested in various aspects of Banjar community life, particularly in the practice of the bagarumutan tradition. Bagarumutan, which originates from the word "garumut" meaning to gather, with the prefix "ba" (which means 'ber' in Bahasa Indonesia), translates to berkumpul or gathering. Gathering to carry out a task collectively or to help each other. In this framework, the Banjar community actively engages in social activities such as bagarumutan in events such as baaruhan or selamatan (religious feasts), pengantinan or wedding receptions, and haul (commemoration) ceremonies. The Banjar people view such events as important moments that motivate them to work together as a communal unit. In-depth analysis of the bagarumutan practice also reveals that religious and traditional values play a significant role in strengthening and preserving the spirit of altruism in Banjar society. Furthermore, this research highlights the importance of bagarumutan in reinforcing local cultural identity and maintaining social bonds amidst the currents of globalization and modernization.